2019
DOI: 10.1212/wnl.0000000000007642
|View full text |Cite
|
Sign up to set email alerts
|

Width and neurophysiologic properties of tissue bridges predict recovery after cervical injury

Abstract: ObjectiveTo assess whether preserved dorsal and ventral midsagittal tissue bridges after traumatic cervical spinal cord injury (SCI) encode tract-specific electrophysiologic properties and are predictive of appropriate recovery.MethodsIn this longitudinal study, we retrospectively assessed MRI scans at 1 month after SCI that provided data on width and location (dorsal vs ventral) of midsagittal tissue bridges in 28 tetraplegic patients. Regression analysis assessed associations between midsagittal tissue bridg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 46 publications
1
48
0
Order By: Relevance
“…Tissue bridge data from a small subset of the study population was previously reported in a different context. [9][10][11]…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue bridge data from a small subset of the study population was previously reported in a different context. [9][10][11]…”
Section: Experimental Designmentioning
confidence: 99%
“…7 8 Preserved tissue bridges adjacent to the intramedullary lesion cavity, which can be identified in all patients with incomplete SCI, 9 are permissive for electrophysiological information flow and the size of which is predictive of functional recovery. [9][10][11] Importantly, NP below the level of injury develops over time. 12 This suggests that fractions of sensory pathways within preserved tissue bridges become active over time and may affect both ascending and descending modulatory systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Vallotton et al 5 retrospectively measured the width of dorsal and ventral tissue bridges on either side of the posttraumatic cyst and their correlation with long-term recovery. The authors show how MRI data taken at 1 month post SCI can be useful in determining relevant functional outcomes at 3 and 12 months post SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Vallotton et al 5 show how measuring the individual widths of dorsal and ventral tissue bridges at 1 month following injury can be used to separately consider the long-term sensory or motor outcomes. This adds a further degree of detail for clinicians to take advantage of when trying to determine the likelihood and extent of recovery.…”
Section: Discussionmentioning
confidence: 99%